Impact of Zinc Fertilization on Tomato (Solanumlycopersicum L.) Yield, Zinc use Efficiency, Growth and Quality Parameters in Eastern Dry Zone(EDZ) Soils of Karnataka, India - Ramamurthy, V.; Sathish, A.; Subbarayappa, C. T.; Prasad, P. N. Siva (Sciencedomain International, 2021)
The present investigation was carried out with one green house experiment at the University of Agricultural Sciences, Bangalore during 2016-17 and two field experiments during 2017-18 at tomato growing soils of eastern dry zone (EDZ), Karnataka to assess the impact of zinc on tomato. Results suggested that all parameters were significantly improved in both deficient and sufficient soils upon the addition of external zinc along with RDF. The treatment T9 in high zinc soils significantly improved the quality parameters like TSS (6.00⁰Brix), titratable acidity (0.39%), Vitamin C (53.71 mg 100 g-1), lycopene (13.24 mg 100 g-1) and shelf life (24 days) when compared with other treatments. The zinc uptake and zinc use efficiency was recorded higher in T9 as 238.91 g ha-1 and 2.47% which is more than that of RDF. But in low zinc soils treatment T10 significantly improved the quality parameters like TSS (5.80⁰Brix) which is on par with T9 (5.90⁰Brix), titratableacidity (0.47%), Vitamin C (55.24 mg 100 g-1), lycopene (13.30 mg 100 g-1) and shelf life (23 days).The zinc uptake and zinc use efficiency was recorded higher in T10as 291.53 g ha-1 and 2.64% which is more than that of RDF.
Keywords: 2. Zero hunger; 6. Clean water